Telework and Women : Case of Women Workers in the Northern States Of Malaysia - Karia, Noorliza; Asaari, Muhammad Hasmi Abu Hassan (2006)
Telework concept is new to women workers in the northern states of Malaysia. Further drastic measures need to be carried out by the government, agencies and organizations in the region to adopt the telework arrangement. Women workers were explored in their acceptance level on telework arrangement. Further, results indicated that women workers in the region do look forward for the telework arrangement to be implemented by their organizations.